2021
DOI: 10.1098/rstb.2020.0234
|View full text |Cite
|
Sign up to set email alerts
|

Vocal learning in animals and humans

Abstract: One contribution of 21 to a theme issue 'Vocal learning in animals and humans'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 36 publications
2
19
0
Order By: Relevance
“…It is doubtful that vocal tremor evolved to signal stress or exertion: most likely, this is simply a physiological side effect of muscular activity, and thus a cue rather than a signal ( Maynard Smith & Harper, 2003 ). It is particularly interesting that such indexical vocal cues are found in humans—a species whose flexibility of vocal control and capacity for vocal production learning are rivaled by songbirds, but few other mammalian species ( Vernes et al, 2021 ). Vocal learners can sometimes escape from physiological constraints on voice production: for example, in-flight vocalizations tend to be synchronized with wing beats in most birds, but not in the species capable of vocal learning ( Berg, Delgado & Mata-Betancourt, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is doubtful that vocal tremor evolved to signal stress or exertion: most likely, this is simply a physiological side effect of muscular activity, and thus a cue rather than a signal ( Maynard Smith & Harper, 2003 ). It is particularly interesting that such indexical vocal cues are found in humans—a species whose flexibility of vocal control and capacity for vocal production learning are rivaled by songbirds, but few other mammalian species ( Vernes et al, 2021 ). Vocal learners can sometimes escape from physiological constraints on voice production: for example, in-flight vocalizations tend to be synchronized with wing beats in most birds, but not in the species capable of vocal learning ( Berg, Delgado & Mata-Betancourt, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is remarkable because vocal learning appears to evolve relatively easily across the animal kingdom (Vernes et al, 2021 ) although usually for functions related to reproduction or social cohesion. Examples are birdsong (Doupe & Kuhl, 1999 ) and or the song of cetaceans (Janik, 2009 ), dolphin whistle imitations (Janik, 2000 ) or vocal convergence in primate social groups, usually as a means to signal social closeness (Ruch et al, 2018 ).…”
Section: Evolution Of Vocal Controlmentioning
confidence: 99%
“…In efforts to resolve this uncertainty, the past half-century has seen a rise in comparative studies investigating the extent to which language-specific traits are also present in more simple forms in nonhuman animals [7][8][9]. Such research has revealed analogues of traits, previously thought to be uniquely human, are also observed in several lineages (including functional referentiality [9][10][11], intentionality [12,13] and vocal learning [14,15]). These studies highlight the importance of the comparative research method when investigating language's origin, as a valuable tool to provide insight into the evolutionary paths of language-specific abilities [16][17][18].…”
Section: Introductionmentioning
confidence: 99%